The impact of ethnicity on the clinical presentations of spinocerebellar ataxia type 3. (March 2020) - Gan, Shi-Rui; Figueroa, Karla P.; Xu, Hao-Ling; Perlman, Susan; Wilmot, George; Gomez, Christopher M.; Schmahmann, Jeremy; Paulson, Henry; Shakkottai, Vikram G.; Ying, Sarah H.; Zesiewicz, Theresa; Bushara, Khalaf; et al.
Abstract: Background: For a variety of sporadic neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis, it is well-established that ethnicity does affect the disease phenotypes. However, how ethnicity contributes to the clinical symptoms and disease progressions in monogenetic disorders, such as spinocerebellar ataxia type 3 (SCA3), remains less studied. Methods: We used multivariable linear and logistical regression models in 257 molecularly-confirmed SCA3 patients (66 Caucasians, 43 African Americans, and 148 Asians [composed of 131 Chinese and 17 Asian Americans]) to explore the influence of ethnicity on age at onset (AAO), ataxia severity, and non-ataxia symptoms (i.e. depression, tremor, and dystonia). Results: We found that Asians had significantly later AAO, compared to Caucasians (β = 4.75, p = 0.000) and to African Americans (β = 6.64, p = 0.000) after adjusting for the pathological CAG repeat numbers in ATXN3 . African Americans exhibited the most severe ataxia as compared to Caucasians (β = 3.81, p = 0.004) and Asians (β = 4.39, p = 0.001) after taking into consideration of the pathological CAG repeat numbers in ATXN3 and disease duration. Caucasians had a higher prevalence of depression than African Americans (β = 1.23, p = 0.040). Ethnicity had no influence on tremor or dystonia. Conclusions: Ethnicity plays an important role in clinical presentations of SCA3 patients, which could merit further clinical studies and public health consideration. These results highlight the role of ethnicity in monogenetic, neurodegenerative disorders. Highlights: Ethnicity plays a role in clinical presentations of SCA3. Asian SCA3 patients have significantly older age of disease onset. African American SCA3 patients have more severe ataxia. Caucasian SCA3 patients more commonly have depression. Ethnicity has distinct impact on motor and non-motor symptoms of SCA3.